TYPES OF LOGISTICS OUTSOURCING: https://doi.org/10.5281/zenodo.15468868 - Kulmurzayeva , Balnur; Yuldashev, Abduhakim (Journal of Contemporary World Studies, 2025)
This article discusses the concept of logistics outsourcing and its importance in the modern economy. The main focus is on various forms of outsourcing of logistics services to external organizations - that is, types of outsourcing. In particular, the levels of outsourcing such as 1PL (first-level logistics), 2PL, 3PL, 4PL and 5PL, their functions, advantages and disadvantages are analyzed in detail. Each type of outsourcing is considered based on real examples and their areas of application are analyzed. The role of logistics outsourcing in optimizing company costs, its impact on service quality, and its role in increasing competitiveness are also considered. Methods of managing logistics services are covered.